Do Interlocks Lead to the Convergence of Interfirm Innovation Performance? Evidence From China. (April 2021) - Teng, Ying; Gimmon, Eli; Lu, Wentong
We examine how interlocking directorates influence innovation performance differentials between firms. Our study offers a new perspective of the effect of interlocking directorate ties upon innovation performance, focusing on network effects on interfirm performance. Using a sample of China's listed companies for the period 2012–2016, we empirically examined the relationship between board interlocks and interfirm innovation performance differentials. The results demonstrate that the presence of board interlocks reduces interfirm innovation performance differentials and leads to a convergence of innovation performance between the connected companies. Furthermore, cross-level analysis found that the relationship between board interlocks and interfirm innovation performance differentials is moderated by the interfirm industry attributes and demographic characteristics of the board. This study expands the existing research in explaining the driving mechanism of enterprise innovation performance as affected by interlocking directorate ties.